2007
DOI: 10.4314/wiojms.v3i2.28459
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Penaeid Shrimp Density, Spatial Distribution and Size Composition in four adjacent habitats within a Mangrove-Fringed Bay on Inhaca Island, Mozambique

Abstract: Abstract-The effects of habitat characteristics (mangrove creek, sandflat, mudflat and seagrass meadow) water salinity, temperature, and depth on the density, spatial distribution and size distribution of juveniles of five commercially important penaied shrimp species (Metapenaus monoceros, M. stebbingi, Fenneropenaeus indicus, Penaeus japonicus and P. semisulcatus) were investigated during a high shrimp recruitment peak lasting from January to June 2002, in four contiguous habitats within a non-estuarine mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
18
0
5
Order By: Relevance
“…The upper Mfolozi and the mouth supported a small community of M. lepidactylus, and the mouth alone supported a M. japonicus population (Table 2). De Freitas (1986) and Macia (2004) reported quite distinct habitat separation between penaeid prawn species in Inhaca Bay, with M. japonicus being found predominantly in sandy areas, F. indicus and P. monodon showing strong preference for muddy mangrovefringed channels, P. semisulcatus preferring submerged vegetation, while M. monoceros were equally abundant in different habitat types. Fenneropenaeus indicus has also been shown to prefer muddy areas associated with mangrove swamps in other estuarine systems (Forbes and Demetriades 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The upper Mfolozi and the mouth supported a small community of M. lepidactylus, and the mouth alone supported a M. japonicus population (Table 2). De Freitas (1986) and Macia (2004) reported quite distinct habitat separation between penaeid prawn species in Inhaca Bay, with M. japonicus being found predominantly in sandy areas, F. indicus and P. monodon showing strong preference for muddy mangrovefringed channels, P. semisulcatus preferring submerged vegetation, while M. monoceros were equally abundant in different habitat types. Fenneropenaeus indicus has also been shown to prefer muddy areas associated with mangrove swamps in other estuarine systems (Forbes and Demetriades 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Primavera (1998) observed that three shrimp of the genus Metapenaeus (Wood-Mason, 1891) presented spatial partitioning based on different salinities and types of sediments. Macia (2004) and Costa et al (2008) reported that juveniles of different Penaeidae species use different areas for nursery habitat to complete their life cycle. According to these authors, the spatial or temporal differentiation observed in closely related species can be due to avoidance of competition for food and territory.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to examine habitat preference in other penaeids (e.g. Hughes 1966, Macia 2004, Gribble et al 2007), but their methods tested for association with habitat rather than preference per se (see Underwood et al 2004 for distinction). Key exceptions include studies on juvenile Penaeus aztecus, P. esculentus and P. semisulcatus, which display similar affinities for complex habitats as reported here, studies on juvenile P. setiferus, which exhibit no preference for either vegetated or un-vegetated habitat (Minello & Zimmerman 1985, Hill & Wassenberg 1993, Kenyon et al 1997, and studies on juvenile Melicertus latisulcatus, which selected bare sand over vegetated habitat regardless of diel period (Tanner & Deakin 2001).…”
Section: Habitat Preferencementioning
confidence: 99%
“…Despite abundant data supporting these theories in other species (e.g. Loneragan et al 1997, Primavera 1997, Macia 2004, it is still unclear whether the immediate cause of higher densities of P. plebejus within macrophyte beds is simply a result of lower post-settlement mortality (via predation or starvation) within this habitat or an innate preference for macrophyte beds during settlement. If P. plebejus postlarvae show a preference for structured habitats, then behavioral mechanisms could be influencing their distribution before post-settlement mortality through predation or starvation.…”
Section: Introductionmentioning
confidence: 99%